The habit of bathing, washing, and defecation habits with malaria events in Pagedongan, Banjarnegara - Hastuti Tongkodu; Tri Baskoro Tunggul Satoto; Trisno Agung Wibowo (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
PurposeThe purpose of this study was to determine the risk factors associated with the incidence of malaria in Pagedongan, Banjarnegara.MethodA cross-sectional study was conducted involving 262 respondents in Pagedongan, Banjarnegara. GPS is used to determine the coordinate points of the respondent's house.ResultsThe prevalence of malaria increased 1.2911 times greater in people who bathe, wash, and defecate outside of the house compared with malaria prevalence in people who did not bathe, wash, defecate outside the house, and are statistically significant (P = 0.0021).ConclusionThe use of mosquito nets, the use of mosquito coils, night out, washing, bathing, defecation the presence of gardens is a statistically significant risk factor for malaria incidence. In addition, there was found a clustering of cases (primary cluster) of malaria incidence and was statistically significant. Education on the importance of using mosquito nets, and the use of mosquito repellent, to avoid mosquito bites at night sleep need to be done, 3M implementation program also needs to be improved.